Prophylactic Topical Tranexamic Acid versus Placebo in Surgical Patients: A Systematic Review and Meta-Analysis - Wan Yi, Teoh; T G, Tan; K T, Ng; K X, Ong; X L, Chan; Samuel Ern Hung, Tsan; Chew Yin, Wang (BJS, 2020)
Introduction: Tranexamic acid (TxA) is used in surgery to reduce blood loss. However, its safety profile is unclear. This review examined the efficacy and safety profile of topical TxA. Method: Electronic databases including Medline and EMBASE were searched from inception to May 2019. Randomised controlled trials (RCTs) published in English comparing topical TxA with placebo were included. Primary outcomes were mortality and blood transfusion incidence. Secondary outcomes included venous thromboembolism. Result: 7,539 patients from 71 RCTs were analysed. Compared to placebo, topical TxA reduced blood transfusion incidence (OR 0.30, 95%CI [0.26 - 0.34], p<0.001). Topical TxA use had no impact on mortality (OR 0.78, 95%CI [0.45 - 1.36], p = 0.39). Pulmonary embolism (OR 0.73, 95%CI 0.27 to 1.93, p = 0.52) and deep vein thrombosis (OR 0.79, 95%CI [0.65 to 1.77], p = 0.79) were not associated with topical TxA use. Conclusion: Topical TxA is effective in reducing transfusion need in surgery without association to major adverse events. However, its optimal dosing regime remain to be determined.